Comparison of the B vitamin composition of milk from mothers of preterm and term babies. Issue 5 (May 1983) - Ford, J E; Zechalko, A; Murphy, J; Brooke, O G
Abstract : Samples of milk were taken at intervals during lactation from 35 mothers of term and 26 mothers of preterm infants and assayed for 8 B complex vitamins. Both term and preterm milks varied widely in vitamin content between mothers. Mean concentrations of thiamin, vitamin B6, nicotinic acid, pantothenic acid, biotin, and folic acid increased progressively over several weeks after parturition but vitamin B12 concentrations declined generally and riboflavin values showed little change. Preterm milk was not richer in vitamins than term milk of the corresponding stage of lactation and it appeared that intake of B vitamins differed widely among preterm infants given their own mothers' milk. These infants may have meagre body reserves and an increased need for vitamins, and breast milk whether from their own mother or from the milk bank may not meet their needs. There is a strong case for supplementing breast milk given to preterm babies with the B complex vitamins.